PEMBERDAYAAN MASYARAKAT DALAM PEMANFAATAN ECENG GONDOK UNTUK MENDORONG KESEJAHTERAAN DI DESA KEBONDOWO KECAMATAN BANYUBIRU KABUPATEN SEMARANG - Sofi Munfaati; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Community empowerment is an effort to provide power or reinforcement to the community. Empowerment was being carried out in various villages in Indonesia to provide strength for the community to move forward and be independent, as was done in the Kebondowo Village, Banyubiru District, which empowered the community by utilizing the water hyacinth as a craft. The intended utilization was to use water hyacinth which thrives in Rawapening as a raw material for making crafts that have a high selling value. The existence of natural resources in the form of water hyacinth became one of the support to the community empowerment. The Kebondowo Village Government formed community empowerment from 2010. This study used descriptive qualitative research method, which described a detailed description of the operationalization concepts that was observed. Community empowerment in the utilization of water hyacinth in Kebondowo Village was explained by looking at the 4 indicators of successful empowerment, namely access, participation, control and welfare. As well as looking at the driving factors and inhibiting factors of the empowerment implementation to improve the welfare of people in Kebondowo Village. Support from all parties that were involved in the community empowerment will help the achievement of community success that improve welfare of Kebondowo Village community to be independent and empowered